Food allergies in children: a comparison of parental reports and skin prick test results - Camilia Metadea Aji Savitri; Azwin Mengindra Putera Lubis; Gatot Soegiarto (Indonesian Pediatric Society, 2018)
Background Food allergy is common in children and its prevalence is generally on the rise. Imprecise parental reports about reactions to particular foods can lead to unnecessary restrictions. Since children have specific growth requirements, such nutritional restrictions may have disturbing effects on children's growth and development. Objective To compare parental reports on food reactions to skin prick test results in their children. Method Retrospective, cross sectional study using patient's medical record data during one-year study period. Data were analyzed manually and statistically, to assess the degree of agreement (Kappa's coefficient) and significance (P). Results We collected data from 154 subjects aged 0-18 years. For every allergen assessed, parents reported more food reactions than positive skin prick test results. Allergy incidence were caused, in order, by cow's milk and chicken (25.3%), eggs (22.1%), chocolate (20.1%), fruits (14.3%), seafood (13%), and saltwater fish (1.9%). Kappa coefficient are all poor (<0.2) and P value are all >0.05 except for chicken (P=0.02). Conclusion Most parents tend to overestimate which food cause reactions in their children, as reactions reported were not necessarily allergenic. Therefore, every patient experiencing allergy reactions should undergo skin prick testing to confirm the possibility of allergy.